Produtividade da beterraba sob diferentes tensões de água no solo, irrigada por gotejamento - Miranda, Jonathan da Rocha (2017)
This work aimed at evaluating the effect of different soil water tensions on beet production, cultivated in a protected environment and under drip irrigation, in a manner to establish criteria for the adequate management of irrigation. The experiment was conducted in the experimental area of the engineering department of Universidade Federal de Lavras (UFLA), in the period from February to May of 2016. A completely randomized blocks design was used, with six treatments and four replicates. The treatments constituted of six soil water tensions (15, 25, 35, 45, 55 and 65 kPa). The soil water tensions were monitored based on the Granular Matrix Sensor – GSM, Watermark®, installed at 0.15 m ( decision sensors) and at 0.3 m (seepage control) of depth. From the results, it was concluded that to obtain higher yield and efficiency of water use, the irrigations must be performed when the soil water tension is at around 15 kPa, at a depth of 0.15m.